Hierarchical geometric constraint model for parametric feature based modeling - Gao, Shuming; Peng, Qunsheng (Journal of computer science and technology, 1997)
A new geometric constraint model is described, which is hierarchical and suitable for parametric feature based modeling. In this model, different levels of geometric information are represented to support various stages of a design process. An efficient approach to parametric feature based modeling is also presented, adopting the high level geometric constraint model. The low level geometric model such as B-reps can be derived automatically from the high level geometric constraint model, enabling designers to perform their task of detailed design.